Senegal : Second Review Under the Policy Support Instrument and Request for Modification of an Assessment Criterion-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key issues related to Senegal's economy. Government proposals for constitutional reforms were approved by 63 percent of the vote in a referendum held on March 20, 2016. Growth was robust at 6.5 percent in 2015 and is projected to continue at a similar level this year. Although the economic outlook remains favorable, downside risks remain. Economic policies and structural reforms are needed to sustain growth and continued fiscal consolidation to meet regional convergence criteria. To keep growth buoyant, steadfast action is needed in following three areas: (1) improving business environment to open economic room for small- and medium-sized enterprises and foreign direct investment; (2) strengthening public financial management and governance; and (3) rebuilding government's fiscal space.